Clinicopathological diagnosis of orofacial granulomatosis - Fatma Sule Afsar; Hatice Demirlendi Duran; Gungor Yilmaz; Murat Ermete (Wolters Kluwer Medknow Publications, 2017)
Orofacial granulomatosis is a rare chronic inflammatory disorder characterized by persistent or recurrent soft tissue swellings, oral ulceration, and other orofacial features in the absence of an identifiable granulomatous disease. We report a case of a 61-year-old woman with recurrent ulcerations and swellings in her oral mucosa. She was diagnosed as orofacial granulomatosis based upon clinicopathological correlation after exclusion of other granulomatous diseases and showed a favorable response to systemic corticosteroid treatment.